The Comparative of Islamic Da'wah and Christian Missionary in Malaysia - Mohd Sukarno Bin Saidi (Universiti Sains Islam Malaysia, 2011)
This study of da'wah methodology and Christian movement. This study is scoped to the conflict faced by Muslims and Christian in spreading their religion. The strength and weaknesses between their two methodologies are the main factor of this study. In effort to achieve the objective, author used field and library studies. Based on the both studies, it has pros and contras besides that, author also try to expose the mission and vision of Christian in effort to expand its influences.